Marketing and Internet professionals' fiduciary responsibility: a perspective on spyware. - Marshall KP; Swartwout N (Journal of Internet Commerce, 2006)
While Internet usage has become a widely accepted marketing vehicle, ethical issues continue to develop without clear guidance. Today controversies abound regarding 'passive devices' technologies for collecting information about Internet users. Passive data collection techniques include such software devices as adware, cookies, spyware, and web bugs. This paper reviews these software devices and presents a 'cultural lag' perspective to explain the lack of clear ethical guidelines for their use. Fiduciary considerations are proposed as a basis for ethical guidelines, codes of ethics of major computer programming, information systems, and marketing professional associations are reviewed, and recommendations are offered to facilitate the development and acceptance of appropriate guidelines.